Profiling Secondary Metabolite of Fresh and Fermented Marigold Flowers and Butterfly Pea Flowers - Ni Luh Putu Kris Monika Yanti; Sukrasno; Defri Rizaldy; Arif Al Iman (Universitas Islam Negeri Alauddin Makassar, 2022)
Communities in Bali use